Effectiveness of Combinied Tera Gymnastics and Emotional Freedom Technique in Reducing Blood Pressure of Older Adults with Hypertension in Karanglewas - Nazwa Arrofa Firdaus; Ragil Setiyabudi; Diyah Yulistika Handayani (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2026)
Background: Hypertension is a chronic condition characterized by persistently elevated blood pressure.. This condition is the fourth leading risk factor for mortality among older adults in Indonesia, with a prevalence reaching 10,2%. Generally, long-term pharmacological therapy is prone to triggeringmedication-related adverse effects. Therefore, non-pharmacological approaches such as physical activity and relaxation therapy  have been shown to beeffective alternatives for controlling blood pressure. To date, no study has examined the combined effect of Tera exercise and the Emotional Freedom Technique on lowering blood pressure, particularly in the Karanglewas Community Health Center (Puskesmas) in Banyumas Regency. Objective: To determine the effectiveness of combined Tera gymnastics and Emotional Freedom Technique in reducing blood pressure among older adults with hypertension.in the Karanglewas Community Health Center (Puskesmas) in Banyumas Regency. Method: This research employed a quantitative quasi-experimental design with a pretest and posttest control group. A sample of 40 older adult was obtained through purposive sampling. Blood pressure measurements used a calibrated digital sphygmomanometer. Data normality was tested using the Shapiro-Wilk test. Data were analyzed using the paired t-test, Wilcoxon, and Mann-Whitney U test. Results: In the intervention group, systolic blood pressure decreased significantly from 144,75 to 140,40 (p =0,001) and diastolic blood pressure also decreased significantly from 89,90 to 81,90 mmHg (p =0,001). In the control group, there were no significant changes in systolic blood pressure (p =0,064) and diastolic blood pressure (p =0,872). The Mann-Whitney test showed a significant difference between the intervention group (systolic delta 5,9 and diastolic delta 10,1) and the control group (systolic delta 0,8 and diastolic delta 0,6) with a p =0,001 result (p ≤0,05). Conclusion: The combination of Tera gymnastics and the Emotional Freedom Technique is effective in reducing blood pressure in the elderly.INTISARILatar belakang: Hipertensi merupakan kondisi meningkatnya tekanan darah yang abnormal. Masalah ini menjadi faktor risiko untuk kematian terbesar keempat pada lanjut usia di Indonesia, dengan prevalensi mencapai 10,2%. Umumnya, pengobatan terapi farmakologis jangka panjang rentan memicu efek samping negatif terkait obat (drug related problems). Oleh karena itu, pendekatan nonfarmakologis aktivitas fisik dan terapi relaksasi menjadi alternatif yang efektif untuk mengontrol tekanan darah. Hingga saat ini belum ada yang meneliti efek gabungan antara senam tera dan Emotional Freedom Technique terhadap penurunan tekanan darah khususnya di wilayah Puskesmas Karanglewas Banyumas. Tujuan: Mengetahui apakah kombinasi senam Tera dan Emotional Freedom Technique efektif dalam menurunkan tekanan darah pada lansia dengan hipertensi di wilayah Puskesmas Karanglewas Kabupaten Banyumas. Metode: Desain kuantitatif kuasi-eksperimen dengan rancangan pretest dan posttest control group diterapkan dalam riset ini. Sampel sebanyak 40 lansia diperoleh melalui teknik purposive sampling (non-probabilitas). Pengukuran tekanan darah menggunakan sfigmomanometer digital yang sudah dikalibrasi. Uji normalitas data menggunakan uji Saphiro Wilk. Analisis data menggunakan Paired t-test, Wilcoxon dan Mann Whitney. Hasil: Pada kelompok intervensi tekanan darah sistolik menurun signifikan dari 144,75 ke 140,40 (p=0,001) dan tekanan diastolik juga turun signifikan dari 89,90 ke 81,90 (p=0,001). Pada kelompok kontrol tidak ada perubahan signifikan pada tekanan darah sistolik (p=0,064) dan diastolik (p=0,872). Uji Mann Whitney menunjukkan terdapat perbedaan yang signifikan antara kelompok intervensi (delta sistolik 5,9 dan diastolik 10,1) dan kontrol (delta sistolik 0,8 dan diastolik 0,6) dengan hasil p=0,001 (p ≤0,05). Simpulan: Kombinasi senam Tera dan Emotional Freedom Technique efektif dalam menurunkan tekanan darah tinggi pada lansia.